Caracterização do desenvolvimento na primeira infância em crianças com Autismo - Gutiérrez, Tesla Gessele Ochoa (Universidade Federal de São Carlos, 2020)
Autism is a neurodevelopmental condition that compromise several development areas Recent research shows that it is possible to identify signs of autism during the first 3 years of life, which is considered the early childhood stage, in which the brain is developing to the maximum possible capacity, being a crucial period for the rest of the children's lives. Likewise, several studies show significant benefits and favorable prognoses for children with autism who receive early intervention, which is the main reason why information should be provided to promote the early identification of autism. Following this concept, this research is based on answering the following question: Do parents of children with autism identify atypical patterns of development during the first 3 years of children's life? Which are those developmental characteristics perceived by the parents? In order to be able to answer these questions, the aim of this research is: To characterize parents' view about the developmental stage of their children with autism, during the stage of 6 months to 3 years of age, and to identify and characterize development-related behaviors found in children with autism during the first 6 months of life up to 3 years of age. In order to perform this study, a type of retrospective study with exploratory and descriptive focus was implemented. Parents of 30 children with autism participated, of whom the children did not exceed the age group of 5 years of age. The parents of children diagnosed with autism were the informants. Data collection was performed through an interview and data analysis was accomplished through the creation of previous categories of social behaviors and measured in content analysis. The results of the research showed that all parents who participated in the research identified atypical behaviors in their children with Autism, before the first 3 years of life of their children. It was possible to categorize social development behaviors into primary categories, of which the most prominent behaviors were regression in the area of communication and shared attention. The study suggests possible research in the area of parental training and regressive autism.
Caracterización del desarrollo infantil en la primera infancia en niños con Autismo
Early childhood development characterization in children diagnose with Autism
Keywords: Educação Especial; Autismo; Desenvolvimento social; Primeira infância; Honduras; Special Education; Autism; Social development; Early childhood; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO